Identification and comparative profiling of gonadal microRNAs in the adult pigeon (Columba livia). Issue 6 (2nd November 2019) - Jiang, L.; Bi, D.; Ding, H.; Ren, Q.; Wang, P.; Kan, X.
ABSTRACT: 1. MicroRNAs are small noncoding RNA molecules that play crucial roles in gene expression. However, the comparative profiling of testicular and ovarian microRNAs in birds are rarely reported, particularly in pigeon. 2. In this study, Illumina next-generation sequencing technology was used to sequence miRNA libraries of the gonads from six healthy adult utility pigeons. A total of 344 conserved known miRNAs and 32 novel putative miRNAs candidates were detected. Compared with those of ovaries, 130 differentially expressed (DE) miRNAs were identified in the testes. Among them, 70 miRNAs showed down-regulation in the ovaries, while another 60 miRNAs were up-regulated. 3. Combining the results of the expression of target gene measurements and pathway enrichment analyses, it was revealed that some DEmiRNAs from the gonad samples involved in sexual differentiation and development (such as cli-miR-210-3p and cli-miR-214-3p) could down-regulate AR (androgen receptor). Cli-miR-181b-5p, cli-miR-9622-3p and cli-miR-145-5p were highly expressed in both the ovaries and testes, which could co-target HOXC9, and were related to regulation of primary metabolic processes. KEGG enrichment analysis showed that DEmiRNAs may play biological and sex-related roles in pigeon gonads. 4. The expression profiles of testicular and ovarian miRNA in adult pigeon gonads are presented for the first time, and the findings may contribute to a better understanding of gonadal expression in poultry.